2005
DOI: 10.1539/joh.47.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy, Age and Sex in the Metabolism of Styrene in Rat Liver in Relation to the Regulation of Cytochrome P450 Enzymes

Abstract: To elucidate the effect of maternal styrene exposure, which is due to various postnatal changes in the development and behavior of offspring, we investigated pregnancy-induced changes in the metabolism of styrene in rat liver in relation to the regulation of cytochrome P450 enzymes. We also examined age and sex-induced changes in the metabolism of styrene. Pregnancy appeared to exert a negative effect on cytochrome P450 content at the late stage, whereas microsomal protein content showed little change during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…The excretion of MA enantiomers showed great difference with the previous study which reported that a small excess of R-MA in workers exposed to air containing styrene and almost racemic MA in orally styrene-dosed Wistar rats [10]. Some factors can influence the metabolism of styrene such as age, sex, pregnancy or drinking alcohol probably via the change of specific P450 isozyme composition or the total content of P450 [11,12]. Linhart et al [4] reported that the ratio of MA enantiomers depends on the stereoselectivity of the formation of MA via styrene oxide as well as on the stereoselectivity of its further oxidation to phenylglyoxylic acid.…”
Section: Assay Of Ma Enantiomers and Pga In Rat Urinecontrasting
confidence: 69%
“…The excretion of MA enantiomers showed great difference with the previous study which reported that a small excess of R-MA in workers exposed to air containing styrene and almost racemic MA in orally styrene-dosed Wistar rats [10]. Some factors can influence the metabolism of styrene such as age, sex, pregnancy or drinking alcohol probably via the change of specific P450 isozyme composition or the total content of P450 [11,12]. Linhart et al [4] reported that the ratio of MA enantiomers depends on the stereoselectivity of the formation of MA via styrene oxide as well as on the stereoselectivity of its further oxidation to phenylglyoxylic acid.…”
Section: Assay Of Ma Enantiomers and Pga In Rat Urinecontrasting
confidence: 69%
“…The data are consistent with rat hepatic microsomal content described in a limited number of postnatal, prepubertal, and pubertal age groups and adults in the literature (Borlakoglu et al, 1993;Kishi et al, 2005). Postnatal changes in microsomal protein content in the rat suggest a need for similar investigations with human pediatric livers (Johnsrud et al, 2003;Johnson et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, characterization of P450 activity in the pregnant rat is an important step towards better understanding of the appropriateness of the rat as a model for drug disposition and fetal safety of xenobiotics during human pregnancy. Several studies using coumarin, progesterone, dehydroepiandrosterone, aminopyrine, styrene, toluene, and trichloroethylene have indicated a general decrease in drug metabolism during pregnancy in the rat although no studies using probe substrates have been published [20,[36][37][38]. The results of this study clearly demonstrate that the effects of pregnancy on cytochrome P450 expression and activity are enzyme-specific and that there is no general "pregnancy effect".…”
Section: Discussionmentioning
confidence: 55%